Celebrity Endorsement Advertising: Brand Awareness, Brand Recall, Brand Loyalty as Antecedence of South African Young Consumers’ Purchase Behaviour - Ndlela, Thubelihle; Chuchu, Tinashe (Journal of Economics and Behavioral Studies, 2016)
Celebrity endorsement advertising has received much attention in recent years from marketing practitioners and academic researchers. Pepsi spent 50 million dollars on an endorsement contract with Beyoncè Knowles which accounted for a sixth of the company’s total budget. This research paper aims to examine whether or not South African marketers can utilise celebrity endorsements to promote their products or brands to young consumers effectively. The other purpose of this study is also to establish whether brand recall, brand awareness, brand loyalty and purchase behaviour are positively influenced by celebrity endorsement advertising. Utilising a quantitative research approach a field study was conducted in Durban whereby research data was collected from 325 participants 18 to 24 years of age. The research survey comprised of 25 questions that were self-administered to willing participants over a one month period. Using SPSS 23 and AMOS 23 software programs, Structural Equation Modeling (SEM) was performed to analyze the data set. Major findings revealedthat brand loyalty is the most significant antecedent of purchase behaviour. Furthermore the study also revealed that participants in the 18-20 year age group were more inclined towards purchasing and paying more for celebrity endorsed brands as compared to any other age group in the survey.Lastly this study provides marketing practitioners an understanding of how firms can benefit from the use as it was found that brand recall and brand loyalty positively influence purchase behaviour whilst brand awareness had no direct influence on purchase behaviour.